PROPORSI PELABELAN BARANG BUKTI JENAZAH YANG DIPERIKSA DI INSTALASI KEDOKTERAN FORENSIK RSUP DR. SARDJITO TAHUN 2012 - , WAHYU JATI P D; , dr. Wikan Basworo, Sp.F. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Corpses sent to forensic experts should be given complete identity attached to toe or other parts of the body. Variable observed in this study is label of corpse evidence comprising label origin, content or corpse identity, and legal aspect of corpse evidence label. Objective: To identify proportion of corpse evidence labeling examined at Forensic Medicine Installation at Dr. Sardjito Hospital 2012. Method: The study used descriptive observational retrospective design. It was conducted in April-May 2013. Data were obtained from secondary data of visum et repertum 2012 and label of corpse evidence and analyzed using tables based on variables. Result: Corpse evidence with label reached 15.7 % and without label 84.3 %. Labels came from Central Java and Yogyakarta Special Territory. Labels 100 % not fully completed content (corpse identity) . Labels that meet legal aspect reached 45.4% and that did not meet legal aspect reached 54.6 %. Conclusion: Proportion corpse evidence supported with label was 15,7 % and without label was 84,3 %. Labels came from Central Java and Yogyakarta Special Territory. Proportion of the completed content (corpse identity) is 100 % not fully completed. Proportion of labels that meet legal aspect reached 45,4 % dan that did not meet legal aspect reached 54,6 %.